Respostas

A melhor resposta!
2012-11-28T23:13:45-02:00

vamos lá.

 

como -x²+5x-6 tem que ser maior igual a 0 então:

 

-x²+5x-60

=> -x^2 + 3x + 2x - 6>= 0

=> -x(x - 3) + 2(x - 3)>=  0

=> (-x + 2)(x - 3)>=  0

=> -x + 2>=  0 e x - 3>=  ou -x + 2 < 0 e x - 3 < 0

=> x  2 e x  3 ou x > 2 e x < 3

logo a solução será {2,3}

 

nota:maior igual o usei como >=

 

1 3 1
2012-11-28T23:36:38-02:00

igual o dele ^^

vamos lá.

 

como -x²+5x-6 tem que ser maior igual a 0 então:

 

-x²+5x-60

=> -x^2 + 3x + 2x - 6>= 0

=> -x(x - 3) + 2(x - 3)>=  0

=> (-x + 2)(x - 3)>=  0

=> -x + 2>=  0 e x - 3>=  ou -x + 2 < 0 e x - 3 < 0

=> x  2 e x  3 ou x > 2 e x < 3

logo a solução será {2,3}

 

nota:maior igual o usei como >=